Kondisi Sosial Ekonomi Orang Tua terhadap Prestasi Belajar - Susanti, Roza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the relationship between the socio-economic conditions of parents on student achievement. Methods and types of research using correlation and quantitative. The population as well as the research sample amounted to 28 students. The research instrument used a questionnaire and the learning achievement of students who took the Educational Profession course. The results showed that the average socioeconomic condition of the parents was 70 with good qualifications and the average learning achievement was 70 with good qualifications. Furthermore, testing using the product moment formula obtained rcount 0.900 and tcount 10.505 with degrees of freedom n-2 (28-2=26), and a significant level of 0.05. The hypothesis is accepted if tcount > ttable. Thus H1 is accepted because the test results prove that tcount is greater than ttable, namely 1,703 > 10,505. The conclusion is that there is a significant relationship between the socio-economic conditions of parents on the learning achievement of students' Educational Professions. Keywords: Parents' Economic Condition, Learning Achievement.